A qualitative study of health care providers' perceptions and experiences of patients bypassing primary healthcare facilities: a focus from Nigeria - Francis G Koce; Gurch Randhawa; Bertha Ochieng (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background The healthcare referral system is designed to ensure that patients receive the best care at the appropriate level, as well as improving access to different levels of care. However, approximately 60-90% of patients in Nigeria bypass their local primary level of care to seek healthcare outside of the community. This study is part of a larger mixed methods study that explored the patients' and healthcare providers' perceptions and experiences in order to understand the factors that influence a patient's decision to bypass the primary level of care to go to secondary and tertiary level facilities. In this study we present the perspectives of the healthcare providers and the factors that influence a patient's decision to self-refer, as well as their suggestions for how primary healthcare facilities can retain patients locally. # Methods In-depth semi-structured interviews were conducted with eighteen healthcare providers comprising doctors, nurses, and community healthcare workers from primary and secondary healthcare facilities in Niger State, Nigeria. The interviews were tape recorded and subsequently transcribed. The analysis was carried out using the principles of framework analysis. # Results The shortage of healthcare providers at local facilities was described as a key reason for patients to self-refer to secondary and tertiary care. Lack of basic equipment, inequitable distributions, and the inconsistent opening hours of the primary healthcare facilities were also considered to be influencing factors for bypassing the primary health facilities. In order to encourage the use of the primary healthcare facilities, some of the healthcare providers suggested ensuring that medical doctors were stationed within those facilities, and also suggested the need for collaboration between the different levels of care, as current services appeared fragmented. # Conclusions Interventions such as employing the services of doctors (family physicians) and standardising the primary healthcare facilities in terms of distribution and availability of the basic facilities are needed to reduce the barriers associated with the bypass of the primary level of care in low cost economies. In addition, tangible policies that ensure the primary health facilities are well resourced should be enacted. The findings have implications for planning, practice, and policy in service delivery aimed at curtailing the bypass of the primary health care facilities.